2020
DOI: 10.3389/fpsyg.2020.560704
|View full text |Cite
|
Sign up to set email alerts
|

Leader Humility and Knowledge Sharing Intention: A Serial Mediation Model

Abstract: PurposeThis paper examines the influence of leader humility on knowledge sharing intention. Drawing on social exchange theory (SET), we test the direct and indirect mechanisms to explain the influence leader humility has on knowledge sharing intention.Design/Methodology/ApproachA two-wave, time-lagged field study was conducted. We surveyed 252 professional employees from Australia.FindingsResults show a significant direct, positive association between leader humility and knowledge sharing intention. While lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 73 publications
(151 reference statements)
1
24
0
Order By: Relevance
“…In other words, even though this study was conducted in a country identified with a high power distance score and authoritarian tendencies (Hofstede, 1991;Hofstede et al, 2005), a humble leadership style remains an essential choice for the community. At the same time, our findings complements the existing literature on the effect of leader humility on positive employee attitudes and behaviors (Carnevale et al, 2019;Lei et al, 2021;Nguyen et al, 2020;Wang et al, 2019) and also the role of leadership in promoting a polite climate (Bunce, 2021;Laschinger and Read, 2016).…”
Section: Theoretical Implicationssupporting
confidence: 81%
See 1 more Smart Citation
“…In other words, even though this study was conducted in a country identified with a high power distance score and authoritarian tendencies (Hofstede, 1991;Hofstede et al, 2005), a humble leadership style remains an essential choice for the community. At the same time, our findings complements the existing literature on the effect of leader humility on positive employee attitudes and behaviors (Carnevale et al, 2019;Lei et al, 2021;Nguyen et al, 2020;Wang et al, 2019) and also the role of leadership in promoting a polite climate (Bunce, 2021;Laschinger and Read, 2016).…”
Section: Theoretical Implicationssupporting
confidence: 81%
“…Previous studies have widely cited social exchange theory (SET) to explain the consequences of leader humility on employee attitudes and behavior (Carnevale et al, 2019;Lei et al, 2021;Nguyen et al, 2020;Wang et al, 2019). SET assumes that a crucial rule in the exchange process is "reciprocity," where the individual reaction of the social exchange process is in response to the actions of others (Blau, 1964).…”
Section: Theoretical Background and Hypothesis Development 21 Leader ...mentioning
confidence: 99%
“…On the one hand, an ex ante approach was adopted in the design of questionnaires ( 56 ). Participants were assured confidentiality and anonymity by an introductive message to minimize social desirability effect ( 57 ). On the other hand, Harman’s single-factor test (SPSS 28.0 version) and the method-factor approach (Mplus 8.3 version) were conducted to ensure statistical control.…”
Section: Methodsmentioning
confidence: 99%
“…Within the context of leader humility, the interplay between agentic and communal values has unique consequences for employees' positive behavior. For example, leader humility is believed to be a predictor of the collaborative environment (Owens & Hekman, 2012a, 2012b, team performance (Rego et al, 2017), psychological capital (Qian et al, 2020), promotion of employees' knowledge-sharing behavior (Anand et al, 2019;Nguyen et al, 2020), and team humility (Ye et al, 2020). Accordingly, leader humility is the basis for driving agentic (dominance and competence) and communal behaviors (cooperation and social bonds).…”
Section: Thriving At Work Ocbmentioning
confidence: 99%
“…Argandona (2015) explains that the main characteristics of a humble leader are openness to the ideas and opinions of subordinates, acknowledging achievements (e.g., giving verbal rewards and acknowledging subordinates' achievements), acknowledging their weaknesses, and willingness to share experiences with subordinates (Argandona, 2015). Therefore, leader humility is closely related to the formation of employee knowledge through their willingness to train subordinates (Nguyen et al, 2020) and creating a collaborative environment (Owens & Hekman, 2012a, 2012b. Although researchers have actively studied the consequences of leader humility on individual and group behavior, its impact on thriving at work has been relatively neglected.…”
Section: Leader Humility Thriving and Ocbmentioning
confidence: 99%